Correlation between Knowldege and Family Support with Active Cadreâs Role - Indrawan, Ida Bagus Made Dwi; Wahjuni, Chatarina Umbul (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTOne factor that canÂ help achievement of 100% UCI village status at Puskesmas is depend on cadreâs role in promoting the importance of immunization to baby mothers and to motivate baby mothersÂ to follow immunization program. The research objective was to analysis factors that related with active cadres roles in UCI village status achievement. This was a cross sectional study Â with sample size used in this research was 63 cadres which is selected by stratified random sampling from UCI village and non UCI village. Result of this research showed Â there were no significant correlation between age ( p = 0,523 ), level of education Â Â Â Â Â Â Â Â ( p = 0,459 ), Â years of being cadre ( p =0,818 ), work status ( p = 0,766 ), attitude ( p = 1,000 ), and posyanduâs acces ( p = 0,713 ) Â with active cadres role. However, chisquare test showed there were correlation between knowledge ( p =0,000) and family support (p = 0,001) with active role cadres. There was no difference of cadreâs role in UCI village and non UCI village ( p = 1,000 ). Conclusion from this research were significant correlation between knowldege and family support with cadreâs role n UCI village achievement. The suggestion for departemen of health Surabaya and Puskesmas is to do refreshing cadres by training regularly to imcrease cadreâs knowledge about immunization.KeywordsÂ : family support, knowledge, active role cadre, attitude, UCI village.